Layer-by-layer cell coating technique using extracellular matrix facilitates rapid fabrication and function of pancreatic β-cell spheroids. (April 2018) - Fukuda, Yasunari; Akagi, Takami; Asaoka, Tadafumi; Eguchi, Hidetoshi; Sasaki, Kazuki; Iwagami, Yoshifumi; Yamada, Daisaku; Noda, Takehiro; Kawamoto, Koichi; Gotoh, Kunihito; Kobayashi, Shogo; Mori, Masaki; et al.
Abstract: Tissue engineering of insulin-secreting cells using alternatives to islet transplantation has been fueled by the development of available materials and fabrication techniques. We have established a cell coating technique that enables the cell surface to be coated with extracellular matrix based on the concept of a layer-by-layer (LbL) assembly. The present study evaluated whether this technique is beneficial for fabricating pancreatic β-cell spheroids using a mouse β-cell line. The well-structured and dense spheroids could immediately be constructed by the LbL-coated cells. In the functional analysis, spheroids with the LbL-coated cells had greater insulin secretion ability with increased expression of the insulin and glucose transporter 2 genes versus spheroids with non-coated cells. In addition, we found that the expression of connexin 36, a gap junction molecule, was upregulated by the LbL cell coating. When spheroids with the LbL-coated cells were syngeneically transplanted in diabetic mice, blood glucose levels immediately decreased and glucose sensitivity significantly improved after intraperitoneal glucose stimulation compared to spheroids with non-coated cells. This cell coating technique would be a clinically applicable approach for fabricating pancreatic β-cell spheroids and treating type 1 diabetes mellitus.